The costs of economic nationalism: Evidence from the Brexit experiment - Born, B; Müller, G; Schularick, M; Sedláček, P (Oxford University Press, 2019)
Economic nationalism is on the rise, but at what cost? We study this question using the unexpected outcome of the Brexit referendum vote as a natural macroeconomic experiment. Employing synthetic control methods, we first show that the Brexit vote has caused a UK output loss of 1.7% to 2.5% by year-end 2018. An expectations-augmented VAR suggests that these costs are, to a large extent, driven by a downward revision of growth expectations in response to the vote. Linking quasi-experimental identification to structural time-series estimation allows us not only to quantify the aggregate costs but also to understand the channels through which expected economic disintegration impacts the macroeconomy.